Physical education in primary school. “Lombardia in gioco” project - Casolo, Francesco; Pignato, Salvatore (Formazione & insegnamento, 2019)
Primary schools have been targeted as privileged settings for the promotion of healthy behaviours and habits for at least four reasons. Firstly, the concept of “active health” lies on the assumption of being able to promote, and consequently induce, an active lifestyle based on recurring physically active habits from the developmental age; secondly, the age range between 6 and 11 is considered a “golden age” for an easier and facilitated learning of the basic motor skills; thirdly, an intellectual-cognitive development and maturation seem to be favoured and facilitated by physical activities and neurodidactic experiences; fourthly, the development and diffusion of citizenship skills can be easily found and/or implemented in movement games, which can be targeted as ideal educational situations to promote the awareness of the importance of rules as well as respect for others and social inclusion, core values of the contemporary society. In the three scholastic years from 2015-16 to 2017-18 the Regional Italian National Olympic Committee (CONI) has been designated by the Lombardy Regional Government to coordinate and manage a project focused on the implementation of physical education (PE) in primary schools in order to promote the development of four critical areas: morphological-functional, affective, cognitive and social. This project named “Lombardia in gioco: una scuola di sport”, in progress also in the current school year (2018-2019), has seen the Università Cattolica del Sacro Cuore of Milan acting as a leader and coordinator of five major Lombardian universities (the University of Milan, the University of Brescia, the University of Insubria of Varese, the University of Pavia). This paper aims to highlight the positive outcomes and the effectiveness of the implementation of this project based on motor and physical education in a primary school context.